GENETIC VARIABILITY AND CORRELATION STUDIES IN F4 POPULATIONS OF UPLAND COTTON - H. Raza; N.U. Khan; S.A. Khan; S. Gul; A. Latif; I. Hussain; J. Khan; S. Raza; M. Baloch (Journal of Animal and Plant Sciences, 2016)
Genetic variability, heritability and correlation studies were carried out among F4 populations of upland cotton during 2014 at the University of Agriculture, Peshawar, Pakistan. Eight upland cotton genotypes i.e. SLH-284, CIM-446, CIM-473, CIM-496, CIM-499, CIM-506, CIM-554 and CIM-707 and their 59 F4 populations were grown in a randomized complete block design with three replications. Genotype means revealed highly significant differences for all the traits. On average, the F4 populations showed best performance than parental cultivars for yield attributing traits and eventually increased the seed cotton yield. Heritabilities (broad sense) were moderate to high in magnitude for all the traits. Major yield components i.e., plant height, bolls per sympodia, boll weight and seeds per boll revealed significant (p≤0.01) positive correlation with seed cotton yield. However, monopodia showed non-significant positive correlation. Overall, the F4 populations CIM-707 × CIM-506 S1, CIM-446 × CIM-284 S2, SLH-284 × CIM-499 S2 and CIM-554 × CIM-473 S2 exhibited maximum boll weight and bolls per sympodia and eventually the seed cotton yield. Results further revealed that F4 populations with larger genetic potential, positive association between yield and yield contributing traits and moderate to high heritability could guide intensive selection for improvement in segregating populations.
Keywords: Genetic variability; correlation; heritability; yield related traits; F4 populations; upland cotton